18F-fluorodeoxyglucose positron emission tomography/computed tomography imaging in atrial fibrillation: a pilot prospective study. (29th May 2021) - Xie, Boqia; Chen, Bi-Xi; Nanna, Michele; Wu, Jiao-Yan; Zhou, Yang; Shi, Liang; Wang, Yanjiang; Zeng, Lijun; Wang, Yuetao; Yang, Xing; Liu, Xingpeng; Yang, Min-Fu
Abstract: Aims: This prospective study explored relevant factors and clinical significance of atrial 18 F-fluorodeoxyglucose (FDG) uptake in patients with atrial fibrillation (AF). Methods and results: One hundred AF patients underwent baseline FDG imaging prior to radiofrequency catheter ablation (RFCA). Of those, 30 subjects underwent additional FDG imaging at 3 months post-RFCA. Voltage mapping of the left atrium was analysed as a voltage score. Patients who received RFCA were followed for 26 months (17–31 months) to assess recurrence. At baseline FDG imaging, 74% of patients with persistent AF (PsAF) and 24% of patients with paroxysmal AF showed increased atrial FDG uptake. The prevalence was higher in the right atrium (49%) than in the left atrium (15%, P  <   0.001) or left atrial appendage (21%, P  <   0.001). Multivariate analysis demonstrated that PsAF and elevated B-type natriuretic peptide (BNP) were related to enhanced right atrial (RA) activity, and increased epicardial adipose tissue (EAT) activity was predictive of left atrial (LA) activity. LA activity was inversely associated with voltage score, while increased FDG uptake in the right atrium was predictive of successful AF termination by RFCA. Atrial FDG activities decreased significantly post-RFCA, but none of the FDG parameters were predictive of AF recurrence. Conclusions: Enhanced RA activity was associated with elevated BNP level, whereas LA activity was related to the increased activity of EAT and inversely correlated with LA fibrosis. Increased RA activity was predictive of successful AF termination by RFCA in PsAF patients.